A Life of Resistance : Ada Prospero Marchesini Gobetti (1902-1968) - Alano, Jomarie (Book collections on Project MUSE., 2016)
"By the time Turin was liberated in April 1945, writer, translator, teacher, and women's rights activist Ada Gobetti had been fighting fascism for almost twenty-five years. This biography, the first in English or Italian, frames her wartime activism in the Resistenza as a chapter in a lifetime of resistance. Ada Gobetti participated in the underground Giustizia e Libertà movement, and helped to found the Partito d'Azione, a political party whose members asked her to represent them as vice mayor of Turin after the war. For Ada Gobetti, the Resistenza also brought an awareness of the specific talents, needs, and rights of Italian women. This led her to organize other Italian women against German occupiers and Fascist oppressors, found an underground women's newspaper, and solidify her views regarding women as a political force. After 1945, resistance meant espousing a set of ideals exemplified by the best that came out of the Resistenza, ideals of grassroots democracy, women's rights, and democratic education for which Ada Gobetti would fight for the rest of her life"--Provided by publisher.